The moderating effect of green innovation on suply chain management and performance (Gestão & Regionalidade, 2016)
The objective of this paper was to investigate the moderating effect of green innovation in the relationship between supply chain management and performance concerning Brazilian companies of the chemical sector. First, we carried out a preliminary study consisting of in-depth interviews with eight chain managers in order to know green innovation in business and develop a questionnaire to collect data. After having undergone pre-tests with seven experts in chain management, the questionnaires were sent to companies within chemical sector, resulting in 316 usable responses, which were treated by hierarchical linear regression and revealed that proactive green innovation profile was able to moderate the relationship between supply chain management and performance. This result showed that the chemical companies have awakened to green supply chain management with attitudes that go beyond regulations, through integration of green initiatives to improve environmental performance.